Development of the financial flow model for the sustainable development of an industrial enterprise - Farida F. Galimulina; Marina V. Shinkevich; Naira V. Barsegyan (Journal of Risk and Financial Management, 2023)
The review of modern methodological approaches to assessing the sustainable development of an industrial enterprise revealed the absence of generally accepted integral tools and the connection sustainable development trends with financial flows. To fill this gap this, taking into account the principle of balanced development economic, environmental and social components aimed. The purpose of the study is the development of a financial flow management model for the sustainable development of an industrial enterprise (using the example of a large Russian petrochemical enterprise). To achieve the goal of the purpose, the following methods implemented systematic approach, analysis and synthesis, comparative analysis, analysis of dynamics series, correlation analysis, regression analysis, solving the linear programming problem. As a result of the study, we came to conclusion about the shift of the enterprise's focus on environmental issues; the growth of the integral indicator of sustainable development of an industrial enterprise; the negative impact of credit resources on the aggregate indicator. The novelty of the study lies in the development of a new methodological solution, which is the basis of the financial management model for the sustainable development of the enterprise: it is adequate to the level of microeconomic system; covers three ways of measuring sustainable development and the possibility of choosing the best quality; allows to implement a proactive approach to managing financial flows with the principles of sustainable development of the enterprise (existing approaches either represent only a set of indicators or addressed the diagnosis of a specific subsystem, either do not consider the relationship between financial flows and the aggregated indicator of sustainable development of the enterprise).
Keywords: 650; economic and mathematical model; financial flows; industrial enterprise; integral assessment; investments; sustainable development